In-hospital Outcome of Acute Coronary Syndrome Patients with on-Admission Hyponatremia (Cardiovascular Journal, 2019)
Background: Coronary artery disease is the commonest form of heart disease and the leading cause of morbidity and mortality throughout the world. Electrolytes imbalance can lead to increase in hospital mortality and morbidity in acute coronary syndrome patients. Our objective was to find out and to compare in-hospital outcome of patients presenting with acute coronary syndrome with or without onadmission hyponatremia.Methods: A total of 336 patients were included in this study of which 59 patients were in group A (sodium level